Analysis of visual appearance of retinal nerve fibers in high resolution fundus images: a study on normal subjects - Kolar, Radim; Tornow, Ralf P; Laemmer, Robert; Odstrcilik, Jan; Mayer, Markus A; Gazarek, Jiri; Jan, Jiri; Kubena, Tomas; Cernosek, Pavel (Computational and mathematical methods in medicine, 2013)
The retinal ganglion axons are an important part of the visual system, which can be directly observed by fundus camera. The layer they form together inside the retina is the retinal nerve fiber layer (RNFL). This paper describes results of a texture RNFL analysis in color fundus photographs and compares these results with quantitative measurement of RNFL thickness obtained from optical coherence tomography on normal subjects. It is shown that local mean value, standard deviation, and Shannon entropy extracted from the green and blue channel of fundus images are correlated with corresponding RNFL thickness. The linear correlation coefficients achieved values 0.694, 0.547, and 0.512 for respective features measured on 439 retinal positions in the peripapillary area from 23 eyes of 15 different normal subjects.
Keywords: Regression Analysis; Healthy Volunteers; Tomography, Optical Coherence; fotografování; axony; retinální gangliové buňky; barva; povrchové vlastnosti; Reproducibility of Results; zdraví dobrovolníci pro lékařské studie; optická koherentní tomografie; lidé; Retinal Ganglion Cells; fundus oculi; Color; regresní analýza; entropie; referenční hodnoty; Algorithms; Fundus Oculi; Humans; Photography; reprodukovatelnost výsledků; počítačové zpracování obrazu; Reference Values; algoritmy; Nerve Fibers; nervová vlákna; Surface Properties; Image Processing, Computer-Assisted; Entropy; Axons